2021
DOI: 10.1111/jori.12339
|View full text |Cite
|
Sign up to set email alerts
|

Should we do more when we know less? The effect of technology risk on optimal effort

Abstract: Technology risk arises when the effectiveness of self‐insurance and self‐protection activities depends on exogenous factors or is only imperfectly known. It affects optimal behavior via a preference channel and a technology channel. In this paper, we identify conditions for unambiguous comparative statics with respect to the presence of, as well as various stochastic changes in technology risk. These conditions involve prudence, relative risk aversion, relative prudence, and several new measures of mitigation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 93 publications
0
7
0
Order By: Relevance
“…Additionally, note that decision makers in Ehrlich and Becker's (1972) setting are assumed to have precise information about the benefits of risk mitigation. In contrast, Li and Peter (2021) analyze self-insurance and self-protection activities where the effectiveness of risk mitigation is subject to exogenous environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, note that decision makers in Ehrlich and Becker's (1972) setting are assumed to have precise information about the benefits of risk mitigation. In contrast, Li and Peter (2021) analyze self-insurance and self-protection activities where the effectiveness of risk mitigation is subject to exogenous environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…In real life, however, promises are not always kept. Reasons for nonperformance include insurer default, claims being denied or contested, delays in the claims handling process, and contractual uncertainty when it comes to the interpretation of the insurance contract (see Schlesinger 2013;Li and Peter 2021). Experiments have shown that individuals tend to react strongly to nonperformance risk, purchasing less insurance than predicted by EU.…”
Section: Nonperformance Riskmentioning
confidence: 99%
“…Regarding the instruments, we set the gross return on saving to R = 1 and specify selfprotection and self-insurance as p (x) = p 0 e −µx and L (y) = L 0 e −νy , where p 0 ∈ (0, 1) is the baseline probability of loss, L 0 the baseline severity of loss, and µ and ν are positive efficiency parameters. Briys et al (1991) use a negative exponential specification for risky self-insurance with uncertain effectiveness (see also Li and Peter, 2021), and Barro (2015) uses this functional form for self-protection in the context of optimal environmental investment. We set µ = 0.0015355 and ν = 0.0012866 in the base case.…”
Section: Preliminaries and Parametersmentioning
confidence: 99%